Therapeutic Development by Targeting the cGAS-STING Pathway in Autoimmune Disease and Cancer - Li, Qiumei; Tian, Shuoran; Liang, Jiadi; Fan, Jiqiang; Lai, Junzhong; Chen, Qi (Frontiers in Pharmacology, 2021)
DNA immune recognition regulation mediated by the cGAS-STING pathway plays an important role in immune functions. Under normal physiological conditions, cGAS can recognize and bind to invading pathogen DNA and activate the innate immune response. On the other hand, abnormal activation of cGAS or STING is closely related to autoimmune diseases. In addition, activation of STING proteins as a bridge connecting innate immunity and adaptive immunity can effectively restrain tumor growth. Therefore, targeting the cGAS-STING pathway can alleviate autoimmune symptoms and be a potential drug target for treating cancer. This article summarizes the current progress on cGAS-STING pathway modulators and lays the foundation for further investigating therapeutic development in autoimmune diseases and tumors.